An Underrated Performer in Repair of Rotator Cuff Tears: Single-row Suture Anchor Technique - Ravi Sharma Pilaka; Varun Kumar Paka; Lavanya Paka; Jameer Shaik; Srivatsava S. Dakshina Murthy Talluri (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Single-row suture anchor technique is a well-established, economical, and relatively easier method of arthroscopic rotator cuff repair that has been recently tripped over by double-row technique which is proven to be biomechanically superior. However, this advantage is not reflected in the functional outcome scores which are reported to be identical with both single- and double-row techniques. Materials and Methods: A prospective cohort study was performed on 67 patients with degenerative rotator cuff tear, diagnosis was confirmed on radiological magnetic resonance imaging, treated surgically by single-row suture anchor method, and evaluated for functional outcome at minimum 1-year follow-up. Pre- and postoperative Visual Analog Scale (VAS) and American Shoulder and Elbow Surgeons (ASES) scores were calculated at initial evaluation and the end of 1-year follow-up. Results: Eighty-six percentage of the patients showed a clinically significant improvement in VAS and ASES scores. Conclusion: Consistent acceptable success rates in terms of outcome functional scores, including patient reported outcomes, depict single-row suture anchor technique as a reliable option for the management of degenerative rotator cuff tears 3 cm or less.